Трудовая активность женщин - Стешенко В. С. Валентина Сергеевна; Пискунов В. П. Владимир Павлович; Чуйко Л. В. Любовь Васильевна; Куценко В. И. (Киев, Наукова думка, 1984)
Авт. указаны на обороте тит. л.